Pengembangan Model Pembelajaran Holistik: Sinergi Antara Olahraga, Bahasa, dan Kearifan Lokal dalam Pendidikan Karakter di Perguruan Tinggi - Z, Muhammad Hidayat; Sari, Mike Nurmalia; Uruk, Febriady Huta (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2024)
Holistic learning in higher education is an approach that integrates various aspects of education, including local wisdom, character education, sports, and language. Sports can help develop motor and health aspects, as well as build a positive and social attitude language, skills in using language, can help control stress, self-control, and develop empathy This approach aims to form individuals who are not only academically intelligent, but also have strong character values and good social skills. This type of research is development research (R&D) with the development procedure adopting the Four-D development model (Define, Design, Develop, and Disseminate) as it develops a holistic learning model: Synergy between Sport, Language, and Local Wisdom in Character Education in Higher Education. Sport as part of holistic learning promotes cooperation, discipline, and physical health, while language acquisition improves communication skills and interpersonal connectedness. This research explores how the integration of these elements can create a more dynamic and effective learning environment and prepare students to face global challenges while respecting local values. The results are expected to contribute significantly to the development of higher education curriculum in Indonesia.